Pengaruh Perawatan Luka dengan Menggunakan Madu Terhadap Penyembuhan Luka Ulkus Diabetikum di Wilayah Kerja Puskesmas Gajah Mada Tembilahan Kabupaten Indragiri Hilir - Hasbi; Putri, Mersi Eka; Tuti, Epu Margias; Ramadia, Arya (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: This study aims to determine the effect of wound care using honey on healing diabetic ulcers in the Gajah Mada Tembilahan Community Health Center Working Area, Indragiri Hilir Regency. Methods: Quantitative research type and pre-experimental design. The research subjects were 12 patients suffering from diabetic ulcers using the Total Sampling technique. The research instruments were the Bates-Jensen Wound Assessment Tool observation sheet and honey. Data analysis uses univariate and bivariate. Results: The univariate results showed that the average diabetic ulcer wound healing score was 56.9 before being given wound treatment with honey and after being given wound treatment with honey the average diabetic ulcer wound healing score was 34.33. The results of the paired t test sample test obtained p.value = 0.000 < 0.05. Conclusion: The conclusion of this research is that there is an effect of wound treatment with honey on the healing of diabetic ulcer wounds in the Gajah Mada Tembilahan Community Health Center Working Area, Indragiri Hilir Regency. The results of this research can be used as a reference for treating Diabetic Foot Ulcer wounds to accelerate healing. Apart from that, we as nurses play an important role in providing knowledge to the public to maintain healthy lifestyle patterns and make them aware of the importance of regularly checking their health status.